Rekonsiliasi Kosmis melalui Tradisi “Nahe Biti”: Tinjauan Etika Diskursus Penyelesaian Konflik Komunal - Fivo Freitas; Hamka Naping; Yahya Yahya; muhammad Basir; Jayana Suryana Kembara (CENDERAWASIH: Jurnal Antropologi Papua, 2026)
The resolution of communal conflicts at the grassroots level often reaches an impasse when relying solely on the state's positive-retributive legal approach, which tends to overlook the psychological and cultural restoration of the community. In Timor-Leste and its border regions, the traditional practice of Nahe Biti ("unrolling the mat") serves as an effective alternative mechanism for restoring post-conflict social relations. This study aims to analyze the communicative structure within the Nahe Biti tradition through the lens of Jürgen Habermas's Discourse Ethics (Diskursethik), exploring how a just peace consensus is locally produced. This study employs a qualitative-descriptive method with a Critical Ethnographic approach. Data were gathered through in-depth interviews with customary elders (Lian Nain), perpetrators, and victims of conflict, alongside participatory observation of the ritual reconstruction. The study reveals that the Nahe Biti tradition actualizes the "ideal speech situation" (ideale Sprechsituation) by flattening social hierarchies through the symbolic unrolling of the mat to ensure the inclusivity of all voices. However, Nahe Biti transcends Habermas’s secular rationality by integrating the dimension of "cosmic reconciliation." Peace does not merely bind human actors but also involves non-human entities (ancestors and nature) through blood sacrifice rituals and customary oaths (Tara Bandu). This study concludes that this cosmological-relational communication model offers a profound critique of Western transitional justice while theoretically contributing to the development of localized restorative justice models in Indonesia and the wider region.